2006
DOI: 10.2217/1745509x.2.5.771
|View full text |Cite
|
Sign up to set email alerts
|

Dignity in Health and Social Care for Older Europeans: Implications of a European Project

Abstract: The use of oral contraceptives is associated with an increased risk of venous thrombosis. It is now generally accepted that women who use oral contraceptives that contain so-called third-generation progestins (desogestrel or gestodene) are exposed to a twofold higher risk of venous thrombosis than women who use oral contraceptives that contain the second-generation progestin levonorgestrel. Coagulation studies demonstrated that oral contraceptives increase the plasma level of prothrombin, decrease the level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…Evidence from practitioners has identified the salience of professional, organisational and institutional influences on dignity in practice (see Tadd and Bayer 2006) but there is limited observational research of practices and little reflection on influences of the care environment on the provision of dignified care. This study pays attention to the contexts in which acute care is delivered and in doing so risk, and the regulation of risk, emerged as a central theme for understanding the everyday practices of delivering care and how older people experienced them.…”
Section: The Study Context and Methodsmentioning
confidence: 99%
“…Evidence from practitioners has identified the salience of professional, organisational and institutional influences on dignity in practice (see Tadd and Bayer 2006) but there is limited observational research of practices and little reflection on influences of the care environment on the provision of dignified care. This study pays attention to the contexts in which acute care is delivered and in doing so risk, and the regulation of risk, emerged as a central theme for understanding the everyday practices of delivering care and how older people experienced them.…”
Section: The Study Context and Methodsmentioning
confidence: 99%
“…Despite the interest and increasing emphasis on dignity within English health policy and in professional codes and research literature, dignity remains difficult to translate into practice, especially in the care of older people. 1-7 Why this is so is not clear. Accounts of older people being treated in undignified ways continue to capture media headlines and challenge care providers.…”
Section: Introductionmentioning
confidence: 99%
“…Gilloran et al 1993;Innes 2002). Recent research has identified that older people prioritize personal identity and autonomy in care provision (Calnan et al 2006), human rights (Woolhead et al 2004), self-esteem, self-worth and well-being (Tadd & Bayer 2006). The actual impact is as yet unknown, but the potential of passive monitoring to undermine these aspects of life for a person with dementia is clear.…”
Section: Working With People Who Are Cognitively Impairedmentioning
confidence: 99%